2017
DOI: 10.1111/1744-7917.12503
|View full text |Cite
|
Sign up to set email alerts
|

Whitefly feeding behavior and retention of a foregut‐borne crinivirus exposed to artificial diets with different pH values

Abstract: Transmission of plant viruses by phytophagous hemipteran insects encompasses complex interactions underlying a continuum of processes involved in virus acquisition, retention and inoculation combined with vector feeding behavior. Here, we investigated the effects of dietary pH on whitefly (Bemisia tabaci) feeding behavior and release of Lettuce infectious yellows virus (LIYV) virions retained in the vector's foregut. Electrical penetration graph analysis revealed that variables associated with whitefly probing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In aphids, stylet activity and movement may be guided/influenced by plant cues such as pH, sugar species and concentration, viscosity, and defense components [20,21] (Figure 2). Whether or not similar plant cues are involved in guiding whitefly stylet activity/movement is not known, but we know that the behaviors of whiteflies feeding on artificial diet of different pH values do not differ significantly [22].…”
Section: Vector Feeding Behaviors Mediating Virus Acquisition and Inomentioning
confidence: 99%
“…In aphids, stylet activity and movement may be guided/influenced by plant cues such as pH, sugar species and concentration, viscosity, and defense components [20,21] (Figure 2). Whether or not similar plant cues are involved in guiding whitefly stylet activity/movement is not known, but we know that the behaviors of whiteflies feeding on artificial diet of different pH values do not differ significantly [22].…”
Section: Vector Feeding Behaviors Mediating Virus Acquisition and Inomentioning
confidence: 99%
“…By using artificial diet, Zhou et al . () studied the effect of dietary pH ( Bemisia tabaci ) on the feeding behavior and retention/release of Lettuce infectious yellows virus (LIYV) virions. They found that whitefly behavior and virus retention were not significantly influenced, but virus release was weakly affected by dietary pH.…”
Section: Transmission and Spread Of Plant Diseases By Vectoring Insecmentioning
confidence: 99%
“…The acrostyle is presumed to retain viruses but also aphid salivary proteins that might interact with plant host signaling; thus, the characterization of this structure and interaction with various proteins will progress the field of virusinsect-plant interactions. By using artificial diet, Zhou et al (2017) studied the effect of dietary pH (Bemisia tabaci) on the feeding behavior and retention/release of Lettuce infectious yellows virus (LIYV) virions. They found that whitefly behavior and virus retention were not significantly influenced, but virus release was weakly affected by dietary pH.…”
Section: Transmission and Spread Of Plant Diseases By Vectoring Insecmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are further backed by biochemical and molecular data supporting the role of the LIYV CPm in mediating the binding of virions to the vector’s foregut [ 10 , 16 , 17 ]. The mechanism underlying the inoculation of LIYV virions retained in the foregut by NW vectors is not understood but may be influenced by the physical properties in the foregut environment such as the dietary pH [ 19 ].…”
Section: Introductionmentioning
confidence: 99%